2017
DOI: 10.1016/j.labeco.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Does professional development of preschool teachers improve children's socio-emotional outcomes?

Abstract: From 2011 to 2013 a randomized controlled trial has been run in Danish preschools to obtain evidence on improvements of early childhood education by providing training to the preschool teachers. The purpose of the intervention is to improve children's socio-emotional outcomes (measured by SDQ), especially for socially disadvantaged children. The teachers in intervention preschools received extra training in implementation of new pedagogical activities and principles, whereas teachers in control preschools did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 44 publications
0
30
0
3
Order By: Relevance
“…One possible explanation for these effects may be that many of the children included in studies come from low-income and poorly educated families (Desimone & Long, 2010). Increasing formal competence by way of structured activities in order to promote the professional knowledge and approaches taken by preschool teachers has also proven to have a positive effect on children's cognitive and social development, as well as their mental health (Jensen, Jensen & Rasmussen, 2015;McCutchen et al, 2002;Piasta, Logan, Pe-latti, Capps & Petrill, 2015). These studies were heterogeneous with regard to the type and extent of the resulting increase in competence.…”
Section: Preschool Impact On the Child -Other Countriesmentioning
confidence: 99%
“…One possible explanation for these effects may be that many of the children included in studies come from low-income and poorly educated families (Desimone & Long, 2010). Increasing formal competence by way of structured activities in order to promote the professional knowledge and approaches taken by preschool teachers has also proven to have a positive effect on children's cognitive and social development, as well as their mental health (Jensen, Jensen & Rasmussen, 2015;McCutchen et al, 2002;Piasta, Logan, Pe-latti, Capps & Petrill, 2015). These studies were heterogeneous with regard to the type and extent of the resulting increase in competence.…”
Section: Preschool Impact On the Child -Other Countriesmentioning
confidence: 99%
“…A study from China showed that having attained specific PD, with resulting a special social status that is related to higher governmental salaries and benefits, was related to higher process quality with a medium effect size (Hu et al, 2016a [64] ). Jennings (2015 [102] ) investigated several aspects of staff-reported well-being, depression, burn out and self-efficacy and relations with observed classroom quality in the United States. The findings showed moderate negative correlations between aspects of depression and burn out with process quality.…”
Section: Structural Characteristics and Process Quality In Ecec: A LImentioning
confidence: 99%
“…Also in Denmark, Germany, France, and Finland several programs are currently carried out or recently completed (Jensen et al, 2013;Jensen et al, 2015;Gasteiger, 2014;Ecalle et al, 2015;and Pakarinen et al, 2011). 2 As the US has been first mover in evaluations of PD in pre-schools, most of the existing evaluations of the effect of PD are related to US experiences.…”
Section: Care Projectmentioning
confidence: 99%
“…We conduct a metaanalysis in which we initially include nine European studies on PD based on data from Denmark, France, Germany, The Netherlands, and Wales. The studies have different focus points despite all being concerned with child outcomes: Literacy, reading or language (Ecalle et al, 2015;Cviko et al, 2014 andHenrichs andLeseman, 2014), matematics (Gasteiger, 2014), or behavior and self-regulation (Hutchings et al, 2013;Jensen et al, 2013;Jensen et al, 2015;Perels et al, 2009 andRönnau-Böse et al, 2009). Thus, after restricting the studies of interest to be concerned with PD effects on child outcomes, there is a lot of variation in the actual outcomes investigated.…”
Section: Care Projectmentioning
confidence: 99%